Mechano-activated connexin hemichannels mediate intercellular glutathione transport and support lens redox homeostasis - Guangyan Wang; Yumeng Quan; Bo Ma; Sumin Gu; Jean X. Jiang (Redox Biology, 2025)
Redox homeostasis and transparency in the ocular lens are closely associated with the distribution of the antioxidant reduced glutathione (GSH). While the synthesis and recycling of GSH have been well characterized, the mechanisms governing its intercellular transport within the lens remain largely elusive. Here, we identified a GSH transport pathway mediated by connexin (Cx) hemichannels in both lens epithelial and fiber cells that has not been fully characterized previously. Through a combination of fluid flow shear stress (FFSS) stimulation, in vitro and ex vivo models, and gene knockout mouse models, we demonstrate that Cx43 and Cx50 hemichannels in lens epithelial cells facilitate GSH efflux in response to mechanical stimuli. Notably, Cx43 hemichannels exhibited higher opening efficiency and greater GSH transport capacity than Cx50 hemichannels under FFSS. The extracellular GSH released from epithelial cells was then taken up by activated Cx50 hemichannels in fiber cells under FFSS, effectively reducing oxidative stress and promoting cell survival. This intercellular relay of GSH between epithelial and fiber cells via mechanosensitive Cx hemichannels suggests a novel mechanism for regulating redox balance within the lens. This pathway may be essential for preserving lens homeostasis and offers new insight into lens physiology and potential therapeutic strategies for preventing or delaying cataract formation.